Religious expression of the main character in no sex in the city novel by Randa Abdel-Fattah - Sita Dian Pratiwi (Fak. Adab dan Ilmu Budaya Universitas Islam Negeri Sunan Kalijaga, 2021)
wt,1/ yna, c.1